Investigating Multidimentional Factors in Zakat Payment Decision among Bank Employee - Nurul Ichsan; Siti Nadhifah (Indonesian Journal of Islamic Economics Research, 2022)
This research aims to analyze the factors that influence the decision of employees of the bank BSISharia central to do zakat. As for the factors that are carefully the level of income, interests, understanding of zakat, work environment and Fintech. The research method used is a quantitative approach with multiple linear regression analysis techniques for H1-H5 testing. The sample in this study was the BSI central bank employees with a number of respondents 40 people. The results of this study show that: in partial there is a significant influence between Income level, interests, understanding of zakat, work environment, Fintech in the decision to pay zakat. if the simultaneous view of the five variables significantly affects the decision to pay zakat. Further studies have been conducted on research discussing the decision of a person by using a variable outside of this study, in order to produce better and more relevant research.